Inferiority Complex in Students of Islamic Studies in Yoruba Region of Nigeria and Implications on Islamic Studies Pedagogy - Khalidu Adewale Afolabi (UIN Sunan Gunung Djati Bandung, 2023)
Across Nigerian tertiary institutions, Islamic Studies is one of the prominent studies in humanities and social sciences. This is due to its quadratic leanings towards religion, sociology, ethics and anthropology. Despite these extensive leanings however, higher studies in Islam is ignorantly perceived and conceived by a mass Yoruba Nigerians as exclusive training for clerical duties in mosques and Muslim evangelism. This derogatory perception has overtime built inferiority complex in students of Islamic studies in Yoruba region of Nigeria as they query their professional relevance beyond religious evangelism in the society. This paper therefore seeks to measure the preponderance of this trait in Islamic students of Yoruba region of Nigeria and investigate its implications on Islamic pedagogy. The paper uses descriptive research method, adopts questionnaire survey design for data gathering and frequency counts and percentages for analysis. It uses multistage sampling for random selection of respondents cutting across extant tertiary institutions in Yoruba region of Nigeria. The paper submits inferiority complex is often extant in students who were offered Islamic Studies without applying for it and argues lack of career focus, economic relevance of Islamic studies and ignorance of course contents are factors responsible for inferiority complex in Islamic studies undergraduates, and this has affected the efficiency and passion for Islamic pedagogy in Nigerian universities.